2020
DOI: 10.1080/14664208.2020.1791533
|View full text |Cite
|
Sign up to set email alerts
|

Agency in language planning and policy

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 63 publications
0
20
0
2
Order By: Relevance
“…Despite these constraining effects, findings also illustrated how participants carved out spaces of agency (Liddicoat & Taylor-Leech, 2021;Menken & Garc ıa, 2010). For instance, many students challenged the accuracy of the exams to measure their academic abilities and suggested that such tests simply served as a test of English regardless of the subject (Abedi, 2004;McNamara et al, 2019;Schissel, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite these constraining effects, findings also illustrated how participants carved out spaces of agency (Liddicoat & Taylor-Leech, 2021;Menken & Garc ıa, 2010). For instance, many students challenged the accuracy of the exams to measure their academic abilities and suggested that such tests simply served as a test of English regardless of the subject (Abedi, 2004;McNamara et al, 2019;Schissel, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Despite the power and presence of high-stakes exams documented above, teachers and students found ways to exert agency (Liddicoat & Taylor-Leech, 2021;Menken & Garc ıa, 2010;Robinson, 2012). In many cases, participants "opened up spaces" of ideological and implementational critique which questioned the appropriateness of the Regents Exams for English learners as well as the validity of any inference made from these test scores (Hornberger, 2005;Menken, 2008).…”
Section: Opening Up Spaces Of Agencymentioning
confidence: 99%
“…Hence, every implementer or actor has their policy regulating government policy according to their environment or circumstances. (Liddicoat & Taylor-Leech, 2020) stated that the theoretical definition of Agency related to implementing LPP involves social actors and intuition in decision-making. They also consider how the Agency is conceptualized in planning and how it can be implemented.…”
Section: Teacher Agency In the Multilingual Education Policy At The S...mentioning
confidence: 99%
“…Research on agency bi / multilingual education is generally conducted outside Indonesia. For example, Liddicoat & Taylor-Leech, (2020) present an overview of the theoretical definition of Agency and how it appears in the concept of LPP by considering how developments in methods and approaches for LPP research focus on social actors and institutions in decision-making. They also consider how an agency can be conceptualized in the planning field, how it can be implemented, and who can exercise Agency.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of globalization, the global level is also an important element in the sociocultural context. In the exploration of policy-practice interrelationship in the education field, agency has been seen as a new issue and context being given prominence in LPP (Liddicoat & Taylor-Leech, 2021). Particularly, learner agency in LPP enactment and implementation at the micro-level has received increasing attention in the literature (Brown, 2015;Phan & Hamid, 2017;Manyukhina & Wyse, 2019;Finardi & Guimarães, 2021;Vennela & Kandharaja, 2021).…”
Section: The Problemmentioning
confidence: 99%